Fishing for Function in the Human Gene Pool. Issue 7 (July 2016) - Barozzi, Iros; Visel, Axel; Dickel, Diane E.
Abstract : Identification and characterization of causal non-coding variants in human genomes is challenging and requires substantial experimental resources. A new study by Tehranchi et al. describes a cost-effective approach for accurate mapping of molecular quantitative trait loci (QTLs) from pooled samples, a powerful way to link disease-associated changes to molecular functions.